Experiences of the Transition to Parenthood in Teenage Married Couples - Aninda Ayu Putri Fuspita Sari; Andari Wuri Astuti; Dwi Ernawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The transition to parenthood is a difficult and stressful time for many couples, and those who become parents in their teens will most likely experience stress and challenges. The objective of this review is to scrutinize evidence related to the experiences of the transition to parenthood in teenage married couples. The scoping review method used was the Arksey and O'Malley framework consisting of 5 stages including identification of the PICO framework, identification of relevant articles, searching for articles from databases such as Science Direct, Pubmed, and Willey, selecting in Prisma Flow Charts, conducting Critical Appraisal on articles, doing data charting, compiling, summarizing, and reporting the results. Based on the search results from the databases, 11 articles were obtained. Of the 11 articles, an assessment was carried out and all articles got a grade of A, 4 articles with the quantitative method and 7 articles with the qualitative method. Furthermore, 3 themes were identified, namely social support, psychological impact, and barriers. The conclusion of the study found a gap in the results of review articles in developed countries and developing countries. In developed countries, the results of review articles tend to focus on psychological problems in the transition to parenthood. The adolescent parents feel pressured and are not ready to become new parents, causing stress and depression when becoming new parents. In contrast to developing countries, psychological problems in the transition to parenthood tend to focus on social support and barriers to becoming new parents. Abstrak: Transisi menjadi orang tua adalah masa yang sulit dan penuh tekanan bagi banyak pasangan apalagi pasangan yang menjadi orangtua pada usia remaja akan berpotensi mengalami stress dan tantangan. Tujuan Review untuk mereview evidence terkait pengalaman transisi menjadi orang tua pada pasangan yang menikah pada usia remaja. Metode scoping review yang digunakan adalah framework Arksey and O’Malley terdiri atas 5 tahap meliputi identifikasi  framework PICO, identifikasi artikel relevan, melakukan pencarian artikel dari database yaitu Science Direct, Pubmed, dan Willey, menyeleksi dalam Prisma Flow Chart, Critical Appraisal pada artikel, melakukan data Charting, menyusun meringkas kemudian melaporkan hasil. Berdasarkan hasil pencarian dari database didapatkan 11 artikel. Dari 11 artikel tersebut dilakukan penilaian dan didapatkan semua artikel mendapat grade A dengan metode penelitian kuantitatif dengan rincian 4 artikel dan metode qualitative study dengan rincian 7 artikel. Selanjutnya didapatkan 3 tema yaitu dukungan sosial,dampak psikologis, dan hambatan. Kesimpulan hasil penelitian ditemukan gap antara hasil review artikel pada negara maju cenderung fokus pada masalah psikologis pada transisi menjadi orangtua, orang tua remaja merasa tertekan dan belum siap untuk menjadi orangtua baru sehingga menyebabkan stress dan depresi saat menjadi orang tua baru, berbeda dengan di negara berkembang masalah psikologis pada transisi menjadi orangtua remaja cenderung fokus pada dukungan sosial dan hambatan menjadi orang tua baru.